A study of the constituents of Tinomiscium philippinense Diels (Fam. Menispermaceae) - Kuyaganont, Swaeng 1926-
A new crystalline principle was isolated from the roots of Tinomiscium philippinense Diels in the form of white needles, m.p. 170(degrees). The compound could be obtained by direct extraction of the powdered drug with ether, or from the alcoholic extracts during the partial recovery of the solvent in the systematic scheme of isolation of the constituents. The crystalline compound gives color reactions with various reagents. Elementary analysis and molecular weight determinations lead to the molecular formula C21H26O6 for the crystalline principle. The crystalline principle contains one methoxyl and one carbonyl group. It forms a 2,4 dinitrophenylhydrazone, (C21H26O5) (NNHC6H3(NO2)2) m.p. 248-251(degrees). Its molecular formula may thus be expanded further to C19H23O4(OCH3) (CO). A tertiary phenolic alkaloid and a quaternary base are also present in the roots. The quaternary base was obtained in the form of picrolonate but it could not yet be obtained pure enough for analysis. The amount of the phenolic tertiary base was vey small and no further work could be done on it.
Available to the general public.
Thesis (Master of Science in Pharmaceutical Chemistry)--University of the Philippines, 1956.
Keywords: Menispermaceae; Tinomiscium philippinense